(untitled) (Andamios, Revista de Investigación Social, 2016)
We present a reflection on the methodological implications of respecting the principle of autonomy in social research. We start from legal considerations and theoretical and ethical principles, based on ethical codes of professional associations’ benchmarks in the field, and the Spanish legislation on protection of personal data. We continue showing how we adapt the theory exposed to methodological idiosyncrasy of research on civic education with minors. We conclude by highlighting the need to reflect on ethical protocols during the phase of ethodological design of research, taking into account ethical and epistemological, and contextual considerations, such as the relative position of the study subjects within the existing power relations where action develops.